Dwelling Time Berpengaruh Terhadap Daya Saing pada Teminal Peti Kemas Internasional di Tanjung Priok - Silaen, Yuli; Siahaan, Langas Denny; Arofat, Osman; Kusmayadi, Dimas Rizki; Yulihapsari, Ika Utami (Institut Transportasi dan Logistik Trisakti, 2025)
The long time required from the time the container is unloaded from the ship arrives with the import customs notification causing loading and unloading activities to be slow at the container terminal at the Jakarta International Container Terminal, Tanjung Priok Port. Another problem is that because goods take a long time to settle, increasing operational costs and the large amount of time needed to wait will be used by competitors as a means of competitivenes. The aim of this research is to determine the direct and indirect influence of service time and Dwelling Time on competitiveness which is mediated by service quality at container terminals. Structural Equation Model - Lisrel is used to determine service quality and competitiveness with simulation scenarios for improvements in loading and unloading quality. This research used a sample of 185 loading and unloading workers from Jakarta International Container Terminal, Tanjung Priok Port. The findings of this research directly and indirectly show that Dwelling Time and service time greatly influence competitiveness through service quality at the container terminal at the Jakarta International Container Terminal, Tanjung Priok Port. The key findings of this research, the existence of Dweling time causes the stockpiling of goods and handling of loading and unloading containers and the use of digitalization tools is required to minimize terminal operational costs and waiting times so that it will increase competitiveness.